Analisis Pola Penggunaan Obat Analgetik Pada Pasien Neurologis di RSUD Padang Panjang - Marjoni, Mhd Riza; Safyanty, Rahmi; Sari, Lidya Puspita (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Neuropathic pain represents a complex clinical challenge and often requires long-term pharmacological therapy. The prescribing patterns of analgesic medications in managing neuropathic pain serve as important indicators for evaluating therapeutic effectiveness, rationality, and individualization. This study aims to analyze the characteristics of analgesic prescribing patterns among neurological outpatients at the Neurology Outpatient Clinic of RSUD Padang Panjang in 2025. A retrospective observational method was employed, involving 100 neurological patient prescriptions selected through purposive sampling. Data were extracted from prescription sheets and patient eligibility forms, then analyzed descriptively to assess prescription characteristics, combination patterns, and diagnostic distribution. The findings revealed that Eperison was the most frequently prescribed medication (71%), followed by sodium diclofenac (56%) and gabapentin (51%). Triple-drug therapy was the most common combination (35%), with sodium diclofenac–eperison–gabapentin being the predominant regimen (40% of triple combinations). The most common diagnosis was low back pain (31.42%), followed by arthrosis (8.57%). The prescribing pattern reflects a polypharmacy approach that integrates muscle relaxants, NSAIDs, and anticonvulsants. The dominance of combination therapies highlights the complex pathophysiology of neurological pain and underscores the need for evidence-based protocol standardization.